The compatibility of reason and revelation in Islam (Quranic approach) - Ashimi, Tijani Ahmad (2015)

(untitled)
Revelation and reason are indeed intertwined in Islamic worldview. Revelation, at least in its Islamic form, seeks its justification in empirical reality; it sees empirical reality as manifestation of a transcendental reality. Therefore, human is linked to the truth of God either through revelation or reason. It is undeniable fact that, reason can guide people to some extent to the broadest universal truths (such as existence of God), it has also contributed immensely to the scientific development and technological advancement in this twenty first century. However, human reason may not be able to provide insight into the details of metaphysical world, such as hell, heaven, creation and eschatology etc... Hence, the role of revelation is emerged to remedy such deficiency that can not be solved by human intellect alone. Thus, it is inadequate to reject revelation and contrast scientific with revealed knowledge. i.e the reality should not be confined exclusively to the realm of visible world and empirical phenomena, under the raison d’etre that reason can not ascertain transcendental reality. As a matter of fact, both revelation and reason are compatible in Islam; for the sake of comprehensive understanding of this universe. Based on this fact, this humble paper will apply Quranic approach to explore vis-a-vis compatibility or integration of revelation and reason in Islam.